2022
DOI: 10.1093/jxb/erac039
|View full text |Cite
|
Sign up to set email alerts
|

Wheat photosystem II heat tolerance responds dynamically to short- and long-term warming

Abstract: Wheat photosynthetic heat tolerance can be characterized using minimal chlorophyll fluorescence to quantify the critical temperature (Tcrit) above which incipient damage to the photosynthetic machinery occurs. We investigated intraspecies variation and plasticity of wheat Tcrit under elevated temperature in field and controlled-environment experiments, and assessed whether intraspecies variation mirrored interspecific patterns of global heat tolerance. In the field, wheat Tcrit varied diurnally—declining from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 76 publications
0
18
0
Order By: Relevance
“…The T-F 0 curve to derive heat tolerance limits is a long-established and widely used technique across ecological and agricultural studies (e.g. Schreiber and Berry 1977;Seemann et al 1984;Hüve et al 2011;Arnold et al 2022;Marchin et al 2022;Posch et al 2022). T crit refers to the point of inactivation and potential damage to PSII, and T max represents its complete disruption (Schreiber and Berry 1977;Smillie and Nott 1979;Terzaghi et al 1989;Knight and Ackerly 2002;Ilík et al 2003;Neuner and Pramsohler 2006;Frolec et al 2008;Hüve et al 2011).…”
Section: Leaf Psii Heat Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…The T-F 0 curve to derive heat tolerance limits is a long-established and widely used technique across ecological and agricultural studies (e.g. Schreiber and Berry 1977;Seemann et al 1984;Hüve et al 2011;Arnold et al 2022;Marchin et al 2022;Posch et al 2022). T crit refers to the point of inactivation and potential damage to PSII, and T max represents its complete disruption (Schreiber and Berry 1977;Smillie and Nott 1979;Terzaghi et al 1989;Knight and Ackerly 2002;Ilík et al 2003;Neuner and Pramsohler 2006;Frolec et al 2008;Hüve et al 2011).…”
Section: Leaf Psii Heat Tolerancementioning
confidence: 99%
“…The active state of Rubisco declines with increasing leaf temperatures and PSII is very sensitive to high leaf temperatures, with heat stress causing unfolding of protein complexes and loss of manganese from the oxygen-evolving complex (Crafts-Brandner and Salvucci 2000;Takahashi and Badger 2011;Jajoo and Allakhverdiev 2017). A common method to quantify PSII Heat Tolerance (PHT) is to measure the critical temperature at which minimal chlorophyll a fluorescence (F 0 ) increases sharply as leaves are heated (Schreiber and Berry 1977;Smillie and Nott 1979;Seemann et al 1984;Knight and Ackerly 2002;Knight and Ackerly 2003;Neuner and Pramsohler 2006;Hüve et al 2011;Arnold et al 2021;Coast et al 2022;Posch et al 2022). This critical temperature indicates a threshold beyond which physiological and photochemical systems have impaired function and where membrane integrity is reduced such that damage might occur if temperatures are sustained.…”
Section: Introductionmentioning
confidence: 99%
“…However, maximum air temperatures before leaf collections ranged by 9.50°C, from 37.22°C to 46.72°C, indicating that strong contrasts in heat exposure were present among sites. One previous study also found no relationship between leaf T crit in wheat and latitude of origin (Posch et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that T crit increases quickly is also supported by past studies using similar methods. For example, Posch et al (2022) reported a 1°C increase in T crit in two genotypes of wheat (Triticum aestivum) after 2 h of 36°C heat shock. Furthermore, Havaux (1993) reported that T crit in detached potato (Solanum tuberosum) leaf discs increased by 4°C from 39 to 43°C in < 1 h and observed a slow return (> 24 h) of T crit after plants returned back to control temperature.…”
Section: The Rapid Rise and Slow Return In T Critmentioning
confidence: 99%